2014
DOI: 10.1111/joid.12029
|View full text |Cite
|
Sign up to set email alerts
|

Throwing in the Towel: Burnout among Practicing Interior Designers

Abstract: Job turnover is often preceded by burnout, a psychological syndrome involving prolonged response to stressors on the job (Maslach & Leiter, 2008). This phenomenon is measured along a continuum ranging from job engaged to full burnout. Higher levels of burnout can result in turnover, excessive absenteeism, and numerous physical and emotional symptoms among employees. The purpose of this study was to assess levels of burnout among practicing interior designers, and identify both individual and situational factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…While information is widely available, it is often widespread and decentralized (Mays & Kossayan, 2011). Moreover, interior designers may be working on multiple projects and are concerned with the number of hours billed to their respective clients (Hill, Hegde, & Matthews, 2014). These concerns can truncate research efforts, as emphasis may be placed on the rapid production of contracted deliverables.…”
Section: Introductionmentioning
confidence: 99%
“…While information is widely available, it is often widespread and decentralized (Mays & Kossayan, 2011). Moreover, interior designers may be working on multiple projects and are concerned with the number of hours billed to their respective clients (Hill, Hegde, & Matthews, 2014). These concerns can truncate research efforts, as emphasis may be placed on the rapid production of contracted deliverables.…”
Section: Introductionmentioning
confidence: 99%
“…First, the transition from academia to practice can be improved within the last academic semester and the first 2–3 years of practice if the individual understands his or her own EI. Mentors in both the academic and professional settings have the opportunity to teach and train the young design professional, who likely has high EI based on the findings of this study, to be ready and able to handle the low MWD that are characteristic of entry‐level positions (Farh et al, ; Hill et al, ). Research based on the methodology established in other professional contexts (Miao, Humphrey, & Qian, ), connecting EI with internship programs and longitudinal studies that follow students into practice to examine how those with high and low EI weathered the professional transition, would likely be incredibly impactful.…”
Section: Research Limitations and Future Research Implicationsmentioning
confidence: 99%
“…The high-stress, deadline-driven nature of the work could be associated with emotionally charged responses by those involved. One study shows that interior designers are experiencing moderate to high frequencies of burnout (Hill et al, 2014), which, coupled with EI research, reveals a possible line of further inquiry in relation to ID professionals. Findings related to student stress in context with team-based design studio projects has suggested that burnout may increase as the same group of students work together repeatedly and that adding student training on team dynamics and conflict resolution could provide some needed relief (Gale, Martin, Martin, & Duffey, 2014).…”
Section: Describes It Wellmentioning
confidence: 99%
See 2 more Smart Citations